Pregnancy intentions in a group of remote-dwelling Australian Aboriginal women: a qualitative exploration of formation, expression and implications for clinical practice - Emma Griffiths (BMC Public Health, 2019)
Abstract Background Unintended pregnancies are associated with poorer obstetric outcomes and are sometimes measured at a population level as a surrogate marker for reproductive autonomy and access to health services, including contraception. Aboriginal Australians face many disparities in health outcomes, including in reproductive health and antenatal care. We aimed to explore the formation and expression of pregnancy intentions in an Aboriginal population to inform health service improvements. Methods Semi-structured interviews were conducted with 27 remote-dwelling Aboriginal women, aged 18–49 years. Content analysis was conducted; key themes were discussed with groups of women from participating communities to refine interpretation. Results Most (19/27) participants expressed pregnancy intentions congruent with reported contraceptive behaviour while eight expressed ambivalent or uncertain intentions. Intentions were shaped by traditional kinship practices, reproductive autonomy and desired family formation. Younger women tended to aspire to smaller family sizes than older women and support was expressed for the postponement of first pregnancy to achieve other life goals. Women in these communities hold strong traditional beliefs, including regarding conception, but did not use traditional methods of contraception in place of modern methods. Reproductive coercion, in the form of pressure to fall pregnant, was recognised as an important issue by women in the community. Conclusion Consultation strategies that promote rapport, allow space for uncertainty and are inclusive of important personal and cultural contexts are likely to improve shared understanding of pregnancy intention. Universal screening for reproductive coercion and broad counselling on contraceptive options (including discrete methods) may reduce unmet need for contraception. Community approaches supporting reproductive autonomy that is inclusive of men, and enhanced educational and occupational opportunities for young women are needed.